Effects of weather and food market risks on household agriculture-nutrition linkage: Micro-level insights from India - Takeshima, Hiroyuki; Saroj, Sunil; Kumar, Anjani (International Food Policy Research Institute, 2023)
Agriculture-nutrition linkages in developing countries remain complex and continue evolving as weather and market risks intensify due to climate change and other geopolitical and socioeconomic factors. Knowledge gaps remain regarding the exact interrelationship among these dimensions of agriculture-nutrition linkages. This study aimed to partly fill this knowledge gap by assessing how the associations between home production of various food groups and household/individual level nutritional outcomes are affected by weather anomalies and price risks of these food groups in the market, using panel data from India. Our results indicate that, generally, the associations between home production and nutritional outcomes are greater under more normal weather, with rainfall and temperature during the production season being closer to the historical median, potentially because of greater productivity realized and sufficient harvest that can be consumed throughout the year. The associations are also greater when households face greater market price fluctuations of food commodities conditional on the distance to the market, potentially because such price risks lead to reduced food purchases from the market. These effects generally hold not only during the average month but also during the lean month, indicating robustness against seasonality. These results also hold more consistently in remote areas than in areas closer to the market. Overall, our results suggest that efforts to promote nutrition-sensitive agriculture in developing countries should also consider evolving patterns of weather risks and agrifood market price risks to improve their effectiveness.